The Implications of Single Euro Payments Area - Mihaita-Cosmin Popovici (CES Working Papers, 2014)
With the creation of the euro by the Maastricht Treaty in 1992, European integration has deepened. Even with this step done the financial market is fragmented. In order to eliminate this disadvantage, the European Union has taken a number of measures. The first step is the Financial Services Action Plan in 2000, through the Lisbon Strategy. Second is the European Commission Regulation 2560/2001 to harmonise fees for cross border and domestic euro transactions. Third is the first pan-European Automated Clearing House in 2003. Last great step made is the Single Euro Payments Area (SEPA) in 2008. In this paper, we want to research the degree of implementation of SEPA by using quantitative indicators: credit transfers, direct debits and payment cards, and the effects of this system on bank efficiency.
Keywords: F15; F36; G29; 330; SEPA; banking; efficiency